Forward osmosis aided concentration of lycopene carotenoid from watermelon juice. Issue 7 (23rd March 2021) - Vani, Bukke; Kalyani, Swayampakula; Pabba, Manideep; Sridhar, Sundergopal
Abstract: BACKGROUND: The world is seeing a substantial rise in the awareness of the health benefits of concentrated fruit juices resulting from their nutritional, functional and sensory properties, which are similar to the availability of natural fresh fruits in the market. Watermelon concentrated juice is enriched with lycopene, an important ingredient used in functional foods such as energy drinks and nutraceutical supplements. Lycopene helps to combat the risk of cancer and heart disease, and has diuretic and anti‐inflammatory properties. Capturing the fresh flavor of watermelon without losing its nutritional value is a real challenge using current manufacturing techniques. RESULTS: The present investigation describes using an indigenous hydrophilized polyamide membrane for the concentration of watermelon juice by forward osmosis (FO). The process enables juice concentration by retaining the original taste, color and nutrient contents. Bench‐scale experimental trials were carried out using the FO process in a countercurrent flow direction at different liquid flow rates of 1.0 to 2.0 L min −1 and draw agent solution concentrations of 0.2 to 1.0 mol L −1 NaCl. The process ensured the recovery of 96.01% lycopene from the concentrated juice, which was found satisfactory with PRO/II simulation, by removal of 70–80% pure water from the juice. Conclusions: The experimental results demonstrated that the lycopene concentration factor showed a 4.14‐fold increase and could be stored successfully at 4 ± 1 °C for 30 days; the degradation of lycopene followed first‐order reaction kinetics. Hence, the pure extracted lycopene can be recommended for use in food, medicine, cosmetics, nutraceuticals, coloring agents and pharmaceuticals. © 2021 Society of Chemical Industry (SCI).